Preparation, characterization and properties of epoxidized palm oil-modified epoxy resin/glass fiber composite / Siti Nur Liyana Mamauod - Mamauod, Siti Nur Liyana (Institute of Graduate Studies, UiTM, 2014)
Surface treatment was carried out on E-glass fiber surface using different concentrations of hydrochloric acid solutions [0.01M-2.0M]. The morphologies of untreated and treated E-glass fiber surfaces were analysed by using scanning electron microscopy (SEM) and the peak of silanol group was identified by using Fourier Transform Infrared (FTIR). The treated glass fiber composites at 0.01MHCI showed the improvement on the tensile properties as compared to untreated and treated glass fiber composites at concentrations ranging from 0.1M to 2.0MHCI. Apart from that, the modified epoxy resin had also been studied by adding epoxidized palm oil (EPO) in the synthetic epoxy resin and it has a potential to partially substitute and toughen synthetic epoxy resin.